Psychosocial Assistance for Elementary School Students Victims of Earthquake through Habituation Program based on Behavioral Approach - Rida Herlina Rojudin; Darozatun Darozatun; Leni Meilani; Tasya Nurfauziah Ridwan; Jonia Lourenca Nunes Brites da Cruz (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The impact of an earthquake disaster that occurred in Cianjur, left physical and psychological injuries that reduced the school spirit of these students, especially SDN Nagrak Cianjur. The purpose of this study was to determine the effect of psychosocial assistance on elementary school students who were victims of the earthquake through a habituation program based on a behavioral approach. The research method uses descriptive qualitative by conducting a literature review. This descriptive qualitative research was aimed at 312 students with the target of assisting 123 students. Habituation assistance to these students is carried out before entering the classroom and outside the room. The habituation activities that are always carried out are, (1) Opening activities; (2) Prayer reading; (3) Singing; (4) mentoring activities; (5) Games; (6) Closing. The results of the habituation assistance show an increase in the sense of enthusiasm to return to school and motivation to learn for students after the earthquake. This habituation includes the moral development of religious values, morals, socio-emotional development, and independence